Vertrauen in Dokumentationen auf der Streaming-Plattform Netflix: Mit einem Vorwort von Prof. Dr. Armin Scholl - Krüger, Lotta (Tectum Verlag, 2023)
Documentaries with opinionated content and one-sided presentations generate high viewer numbers on the streaming platform Netflix. For their success, it is often less relevant whether they also meet the quality criteria necessary for the genre. Therefore, Lotta Krüger examines the viewers' expectations of such Netflix documentaries and to what extent they trust them. Her qualitative study of guided interviews provides an exciting insight into the thoroughly reflected user behavior of the viewers and and sheds light on the media competence of the under 35 years olds.